1991
DOI: 10.1111/j.1600-0560.1991.tb00154.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of fungal organisms in tissue sections using anti‐mycobacteria antibodies

Abstract: Sixty-four cases of deep fungal infections diagnosed using PAS or silver stains and 18 control cases of sarcoidosis, M. tuberculosis and M. leprae infection were stained using commercial polyclonal antibody raised against M. paratuberculosis (MP), M. Duvalii (MD), and Bacillus Calmette-Guerin (BCG). Nine of 13 cases of sporotrichosis stained positively using anti-MP antibody only; 13 of 14 cases of histoplasmosis stained with anti-BCG, anti-MD, and anti-MP; seven cases of cryptococcosis had only focal staining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 8 publications
0
17
0
2
Order By: Relevance
“…Septate hyphae were revealed by both periodic acid-Schiff staining (PAS) and Gomori methamine staining (GMS) inside and outside the macrophages. Immunohistochemistry was performed by the avidin-biotin-peroxidase method (3,22). Antibodies are listed in Table 1.…”
Section: Case Reportmentioning
confidence: 99%
“…Septate hyphae were revealed by both periodic acid-Schiff staining (PAS) and Gomori methamine staining (GMS) inside and outside the macrophages. Immunohistochemistry was performed by the avidin-biotin-peroxidase method (3,22). Antibodies are listed in Table 1.…”
Section: Case Reportmentioning
confidence: 99%
“…The parallel use of different histochemical staining methods (HSM) is time consuming and expensive. There are some reports about the successful application of rabbit polyclonal antibody directed against the Bacillus Calmette-Guérin (BCG) strain of Mycobacterium bovis in the immunohistochemical detection (IHC) of various bacteria and fungi in skin biopsies (Wiley et al, 1991;Kutzner et al, 1998;Bonenberger et al, 2001). Studies in human medicine have shown that polyclonal anti-BCG antibodies cross-react with a broad spectrum of bacteria, fungi and also with a few parasites (Minden et al, 1972;Harboe et al, 1979;Thorns and Morris, 1986).…”
mentioning
confidence: 99%
“…Epitopes of these microorganisms were identified by monoclonal antibodies as being similar to epitopes from mycobacterial antigens (Thorns and Morris, 1986). In the latter investigations anti-BCG antibodies were successfully used for immunohistochemical detection of the most common cutaneous microbial pathogens in formalin-fixed and paraffin-embedded human tissue samples (Wiley et al, 1991;Kutzner et al, 1998). This method was found to be superior to conventional HSM in terms of quality and sensitivity, and it was helpful especially in those cases where only a few organisms were present, obscured by a dense overlying inflammatory infiltrate (Kutzner et al, 1998).…”
mentioning
confidence: 99%
“…Nesta situação, a coloração específica para bacilos álcool-ácido-resistentes (BAAR), métodos de imunohistoquímica e teste tuberculínico são exames importantes para o diagnóstico diferencial. Com freqüência observa-se em formas paucibacilares da doença, que a pesquisa de BAAR, a imunohistoquímica e as culturas são negativas (Hsu et al, 1981;Wiley et al, 1991;Taippeiner, Wolf, 1993;Kox, 1995;Kutzner et al, 1998;Bollela et al, 1999;Ulukanligil et al, 2000;Ferreira et al, 2002).…”
Section: Objetivosunclassified
“…No caso da micobactéria, desenvolveu-se anticorpo primário de imunoglobulina de coelho anti-Mycobacterium bovis (anti-BCG (Beck, Freeman, 1991;Whiley et al, 1991;Kutzner et al, 1998).…”
Section: Imunohistoquímicaunclassified